FAKTOR-FAKTOR YANG MEMPENGARUHI MARKETED SURPLUS PADI DI KABUPATEN SLEMAN - , ESTYATIKA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to (1) determine whether rice farmers in Sleman are a net producer or a net consumer (2) determine the behavior of farmers in allocating rice yields in Sleman (3) determine the factors that influence the level of marketed surplus of rice in Sleman. The basic method is analytical descriptive study, the determination of respondents defined by purposive random sampling, which is based on the characteristics of the location of the sampling distance of the village to the district consisting of 22 farmers in the village farthest from the district and 22 farmers in the nearby villages of the district. Factors that affect the marketed surplus of rice were analyzed using multiple linear regression variables used are rice production, total non-rice income, family size, the price of rice, the distance to the village of the district, and the status of the land. The results showed that (1) farmers in Sleman is a net producer of farmers (2) farmers behavior in allocating rice yields in Sleman district consists of the payment in kind, consumed, and sold to the market (3) Factors affecting marketed surplus of rice in Sleman district is rice production, rice prices, distance to the village of the district, and the status of the land.